Laser Induced Transient Photothermal Radiometry in Opaque Samples - Grozescu, Ionel-Valeriu (1998)
A radiometer system has been designed and constructed for measurements of optical, thermal and related properties of two distinct categories of opaque samples. It was used exclusively for highly light absorbing and/or diffusing samples (protective coatings and ceramics) and highly reflecting samples (metals and its alloys). In the measurements, the signals were initially generated by localised pulsed laser heating of the sample. The signals were then monitored directly by detecting changes in infrared radiation or indirectly by measuring the deflection of the reflected probe beam. The underlying theory behind the technique and the design criteria for the radiometer are discussed. The theory has been described for the case of direct signal detection and as well as for the case of indirect signal detection. The performance of each type of detection was duly evaluated and found that the indirect detection displayed much higher signal-to-noise ratio for the respective intended application.